Uncovering the invisible: a study of Gaia18ajz, a candidate black hole revealed by microlensing - Howil, Kornel; Wyrzykowski, Ł; Kruszyńska, K.; Zieliński, P.; Bachelet, E.; Gromadzki, M.; Mikołajczyk, P. J.; Kotysz, K.; Jabłońska, M.; Kaczmarek, Zofia; Mróz, P.; Ihanec, N.; et al. (Astronomy and astrophysics, 2025)
Context. Identifying black holes is essential for our understanding of the development of stars and can reveal novel principles of physics. Gravitational microlensing provides an exceptional opportunity to examine an undetectable population of black holes in the Milky Way. In particular, long-lasting events are likely to be associated with massive lenses, including black holes. Aims. We present an analysis of the Gaia18ajz microlensing event reported by the Gaia Science Alerts system. Gaia18ajz is a long-timescale event exhibiting features indicative of the annual microlensing parallax effect. Our objective is to estimate its lens parameters based on the best-fitting model. Methods. We used photometric data obtained from the Gaia satellite and terrestrial observatories to investigate a variety of microlensing models and calculate the most probable mass and distance to the lens, taking into consideration a Galactic model as a prior. Subsequently, we applied a mass-brightness relation to evaluate the likelihood that the lens is a main sequence star. We also describe the DarkLensCode (DLC), an open-source routine that computes the distribution of probable lens mass, distance, and luminosity employing the Galaxy priors on stellar density and velocity for microlensing events with detected microlensing parallax. Results. We modelled the Gaia18ajz event and found its two possible models, the most probable Einstein timescales for which are days and days. Applying Galaxy priors for stellar density and motion, we calculated a most probable lens mass of located at , and a less probably mass of located at . Our analysis of the blended light suggests that the lens is likely a dark remnant of stellar evolution rather than a main sequence star.